2004
DOI: 10.1074/jbc.m312799200
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin-associated Inhibition of Intracellular Trafficking Is Attributed to a Co-purified Activity

Abstract: Geldanamycin, an ansamycin antibiotic that specifically inhibits heat-shock protein-90 (HSP90) and its endoplasmic reticulum homologue, glucose-regulated protein-94 (GRP94), accelerates the degradation of selected cellular proteins. We showed previously that geldanamycin inhibits maturation and transport of the epidermal growth factor receptor in addition to accelerating its degradation ( Chromatography of S. hygroscopicus var. geldanus extracts on a silica-gel column allowed separation between the inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…However, additional compounds were observed in these fractions. Through a careful series of semi-preparative reverse-phase HPLC experiments with a phenyl-hexyl column, reblastatin ( 3 ), 5 17- O -demethyl-geldanamycin ( 4 ), 6 19- S -methylgeldanamycin ( 5 ), 7 17-amino-17-demethoxy-geldanamycin ( 6 ), 8 methyl geldanamycinate derivative 7, 9 and recently reported geldanamycin analog 9 were resolved and isolated. 10 There were also two previously unreported metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…However, additional compounds were observed in these fractions. Through a careful series of semi-preparative reverse-phase HPLC experiments with a phenyl-hexyl column, reblastatin ( 3 ), 5 17- O -demethyl-geldanamycin ( 4 ), 6 19- S -methylgeldanamycin ( 5 ), 7 17-amino-17-demethoxy-geldanamycin ( 6 ), 8 methyl geldanamycinate derivative 7, 9 and recently reported geldanamycin analog 9 were resolved and isolated. 10 There were also two previously unreported metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of Hsp90 promotes the attainment and maintenance of proper conformation of its clients, including EGFR, HER-2, Akt, and wild type or mutated androgen receptor, which are of potential importance in mediating prostate cancer progression [17][18][19]. An Hsp90 inhibitor, geldanamycin (GM), has been shown to have two distinct effects on EGFR: promoting its degradation and mediating its intracellular retention [20]. It has also been reported that 17-allyamino-17-demethoxygeldanamycin (17-AAG), a GM-derived Hsp90 inhibitor, could induce the degradation of both wild-type and mutant form EGFR [21].…”
Section: Introductionmentioning
confidence: 99%
“…Sol EPO-R Secretion. BOSC-23T cells expressing sol EPO-R cDNA (41,61) were cultured in 6-cm plates. Confluent cell cultures were incubated at 37°C for 3 h in 1 ml of DMEM containing 0.2% FCS.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were lysed in 0.5 ml of sample buffer X2 and boiled for 15 min. Aliquots of media (40 l) and cell lysates (20 l) were subjected to Western blot analysis (61).…”
Section: Methodsmentioning
confidence: 99%